Video Games and Storytelling: Reading Games and Playing Books - Mukherjee, Souvik (Palgrave Macmillan, 2018)
The potential of video games as storytelling media and the deep involvement that players feel when they are part of the story needs to be analysed vis-a-vis other narrative media. This book underscores the importance of video games as narratives and offers a framework for analysing the many-ended stories that often redefine real and virtual lives.
OCLC: 1040048516
Keywords: 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Gameplay in the “Zone of Becoming”: Locating Action in the Computer Game - Mukherjee, Souvik (Conference Proceedings of The Philosophy of Computer Games 2008, 2009)
Extending Alexander Galloway’s analysis of the action-image in videogames, this essay explores the concept in relation to its source: the analysis of cinema by the French philosopher Gilles Deleuze. The applicability of the concept to videogames will, therefore, be considered through a comparison between the First Person Shooter S.T.A.L.K.E.R. and Andrey Tarkovsky’s film Stalker. This analysis will compellingly explore the nature of videogame-action, its relation to player-perceptions and its loca-tion within the machinic and ludic schema.
Google-Books-ID: SJ972ia4kZQC
Keywords: 1-Cinéma; 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

First-Person Encounters #4: Poornima Seetharaman - Game Studies India Adda (Game Studies India Adda, 2021)
First Person Encounters is a series of podcasts presented by Games Studies India, about our first experiences with Games while growing up in India. This our third podcast where we talk with Poornima Seetharaman. She is the first Indian to be inducted in the Women in Games (WIGJ) Hall of Fame and is also the lead game designer at Zynga. Hear as we talk about her foray in the world of gaming.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé